Through a glass, darkly - Leon, Donna (New York Grove Press, 2006)
An annotated copy of Dante's Inferno, found at the scene of the crime, may contain the clues Brunetti needs to solve the murder - and uncover who is ruining the waters of Venice's lagoon. But Brunetti needs the help of his wife, Paola, a professor of literature, and his daughter, Chiara, who should be doing her Latin homework. Over long lunches, on secret boat rides, and in quiet bars, as the weather heats up, the flowers come into bloom, and the tourists return in droves, Brunetti searches for the night watchman's killer. But can he unravel the poetic clues before the unseemly death is allowed to be forgotten?
Originally published: London : William Heinemann, 2006.
Keywords: Police; Brunetti, Guido (Fictitious character); Watchmen -- Crimes against; Businessmen; Environmentalists; Water -- Pollution -- Italy -- Venice, Lagoon of; Police -- Italy -- Venice; Murano (Italy); Detective and mystery stories; Mystery fiction